Comparative proteomics analysis of adult Haemonchus contortus isolates from Ovis ammon - Liu, Gongzhen; Liu, Qing; Han, Zhaoqing; Wang, Peikun; Li, Yanshen (Frontiers in Cellular and Infection Microbiology, 2023)
Haemonchus contortus is an important parasite that causes disease that seriously endangers ruminant animals cattle, sheep, goat, and camel. Here, we compared the proeomics analysis of three adult Haemonchus contortus isolates from mouflons (Ovis ammon). A total of 1,299 adult worm proteins were identified, and 461 proteins were quantified, of which 82 (108), 83 (97), and 97 (86) significantly upregulated (downregulated) differentially expressed proteins (DEPs) were detected among pairwise comparisons (1-vs.-3, 2-vs.-3, and 2-vs.-1). Liquid chromatography–tandem mass spectrometry (LC−MS/MS) and bioinformatic analysis indicated that these DEPs are mainly concentrated in cellular composition, molecular function, biological function, and catabolism pathways. In addition, Gene Ontology (GO) classification and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were carried out to screen the DEPs. The main biological processes involved were nucleotide, nucleotide phosphate, ribonucleotide, purine-containing compound, purine ribonucleotide, single-organism, oxoacid, organic, carboxylic, oxoacid metabolic processes and single-organism catabolic processes. The majority of KEGG pathways were found to be related to metabolic pathways, biosynthesis of secondary metabolites, biosynthesis of antibiotics, carbon metabolism, and microbial metabolism in diverse environments. Moreover, we also found differences in the expression of some important or novel regulatory proteases, such as serine hydroxymethyl transferase (SHMT), dihydrolipoyl dehydrogenase (DLD), and transket pyr domain-containing protein (TKPD). In summary, label-free proteomic analysis of adult H. contortus worms displayed significant differences in three different individual isolates, which helps to improve our understanding of the growth and metabolic mechanisms of H. contortus in different individuals and relative natural environments and provides novel drug targets for the treatment of parasitic diseases.